2012
DOI: 10.4021/jocmr1106w
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Outpatient Intravenous Diuretic Therapy in a Transitional Care Program for Patients With Heart Failure: A Case Series

Abstract: We present a case series of seven patients with an established diagnosis of heart failure enrolled in a transitional care program that were treated with intravenous diuretic therapy in the outpatient setting. The patients presented in this cases series were treated due to the development of decompensated heart failure within 30 days of their discharge from our hospital. All seven patients stated that they would have originally presented to the emergency department for their symptoms, but consented to alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Ryder and colleagues 126 found that 72% of patients were stabilized and did not require hospitalization, 124 and Banerjee and colleagues 129 noted that 94% of patients were not admitted within 28 days following their outpatient IV diuresis regimen. [126][127][128] Unsurprisingly, considerable cost savings were noted when hospitalization was not required. 126,127,129 Further benefit was seen when outpatients receiving IV diuretics were linked with an HF disease management program.…”
Section: Advance Care Planning Outpatient Intravenous Diuresismentioning
confidence: 94%
See 3 more Smart Citations
“…Ryder and colleagues 126 found that 72% of patients were stabilized and did not require hospitalization, 124 and Banerjee and colleagues 129 noted that 94% of patients were not admitted within 28 days following their outpatient IV diuresis regimen. [126][127][128] Unsurprisingly, considerable cost savings were noted when hospitalization was not required. 126,127,129 Further benefit was seen when outpatients receiving IV diuretics were linked with an HF disease management program.…”
Section: Advance Care Planning Outpatient Intravenous Diuresismentioning
confidence: 94%
“…[126][127][128] Unsurprisingly, considerable cost savings were noted when hospitalization was not required. 126,127,129 Further benefit was seen when outpatients receiving IV diuretics were linked with an HF disease management program. 124,126,127,129 Patients at high risk for recurrent HF exacerbation were closely monitored and able to receive an immediate response to changes in clinical status.…”
Section: Advance Care Planning Outpatient Intravenous Diuresismentioning
confidence: 94%
See 2 more Smart Citations
“…It is geared toward patients who do not require the length or level of services provided by inpatient care but require management beyond traditional ED care [38]. Descriptive studies demonstrated the efficacy of the observation medicine approach (see supplement) [39][40][41]; however, there are no RCTs that examined 30-day revisit rates. Identification of the right patients, right services, right therapies, right length of treatment and right level of care providers that lead to optimal patient safety and best outcomes are needed.…”
Section: Hf Observation Carementioning
confidence: 99%